If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3c = cx + -2 Reorder the terms: 3c + 3x = cx + -2 Reorder the terms: 3c + 3x = -2 + cx Solving 3c + 3x = -2 + cx Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1cx' to each side of the equation. 3c + -1cx + 3x = -2 + cx + -1cx Combine like terms: cx + -1cx = 0 3c + -1cx + 3x = -2 + 0 3c + -1cx + 3x = -2 Add '-3x' to each side of the equation. 3c + -1cx + 3x + -3x = -2 + -3x Combine like terms: 3x + -3x = 0 3c + -1cx + 0 = -2 + -3x 3c + -1cx = -2 + -3x Reorder the terms: 2 + 3c + -1cx + 3x = -2 + -3x + 2 + 3x Reorder the terms: 2 + 3c + -1cx + 3x = -2 + 2 + -3x + 3x Combine like terms: -2 + 2 = 0 2 + 3c + -1cx + 3x = 0 + -3x + 3x 2 + 3c + -1cx + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 2 + 3c + -1cx + 3x = 0 The solution to this equation could not be determined.
| 2+4x=-16+x | | 73y=8(9y+10) | | 5c-3=5x-(x+2)-1 | | N=0.5s+-1z | | 7-1/2x=-4 | | 8x-75=5x-12 | | 5x-18=y | | 5y^2-13y-28= | | 1x-1=5x-4x-4+25 | | -99/x=2 | | 3x+19=56 | | V=(24-2x)(18-2x)x | | -3x+14=-7 | | 9x+7y=19.7 | | 6r^4/r^7 | | 2e^3x-1=e^2x+1 | | 3(3x+5y)-9x-7y=3(19.825)-19.7 | | 2x(x-3)=8(x-3) | | X^8/x^9 | | -8-3=10x+3-9x | | 11x-9y-10= | | a*3+5=12 | | 4x(3x^3y^4)= | | I=F-IR | | 2x^2-20x-48= | | 5x+6x-3=21 | | F-IR=I | | 7/9-3/18 | | F=i+ir | | x^2+3x-2012=0 | | (w)(w+7)=0 | | x-18sqrtx+80=0 |